Transition Time of Ultrasonic Wave as a Tool of Quality Evaluation of Layered Polymer Composites - SZYMICZEK, Małgorzata (Archives of Acoustics, 2017)
Observation of behaviour phenomena of ultrasonic waves in an object allows for quality assessment, identification and location of discontinuity. Physical nature of acoustic processes is based on propagation of mechanical waves constituting a disturbance of equilibrium of the state of material. The acoustic process identified by selected characteristics can be a source of information about state of material, its structure, and properties, which is particularly important for systems exhibiting anisotropy properties, and such are layered polymer composites. They are special materials because their properties depend greatly on the manufacturing technology. Therefore, while conducting acoustic tests which use the influence of elastic properties and homogeneity of material structure for propagation of sound waves the adopted method of measuring characteristics which identifies propagation of ultrasonic wave phenomenon is of particular importance. The aim of the work was quality evaluation of layered polymer composites made by winding and press moulding by the method of echo and C-scan, using head Phased Array. Composites have been tested by thermal and fatigue degradation. Quality evaluation has been made based on the transition time of the ultrasonic wave and the bending strength.